Metode Tarjih Ath-Thabari Dalam Jami' Al-Bayan Fi Ta'wil Al-Qur'an - Baiq Farhan (Jurnal Studi Ilmu Alquran dan Tafsir, 2025)
The tarjih method applied by Imam ath-Tabari in his interpretation of the Qur'an reflects a scientific and rational approach in selecting and prioritizing interpretations that are considered more valid and relevant. In his monumental work, Jami' al-Bayan fi Ta'wil al-Qur'an, ath-Tabari presents various opinions from previous mufassir, both based on history and rational opinion, for each verse that is interpreted. This article was written using library research in order to extract the necessary data from library sources and using qualitative research methods. After the data was collected the author used descriptive-analysis methods in order to produce appropriate conclusions. After presenting various perspectives, ath-Tabari then used the tarjih method to assess and choose a stronger interpretation based on its suitability to the text (nash) and context (sabab al-nuzul) of the verse, as well as the strength of the existing sanad and matan narration. This approach emphasizes the importance of checking the validity of history, as well as connecting interpretations with historical and cultural context. Through his tarjih method, ath-Thabari not only provides a deep understanding of the meaning of the verses of the Qur'an, but also creates space for critical scientific debate between various existing opinions. Thus, al-Tabari's tafsir has become the main reference in classical tafsir studies which prioritize a comprehensive scientific methodology